Method for preparing battery-grade iron phosphate from lithium iron phosphate lithium extraction slag
By pre-pelletizing the lithium iron phosphate extract slag and processing it at high temperature under a reducing atmosphere, converting it into a ferrophosphorus alloy, and then treating and calcining through acid, the problem of difficult separation of impurities and preparing battery-grade iron phosphate in the prior art is solved, and efficient and simple resource utilization is achieved.
Patent Information
- Application Number
- CN202510255430.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The prior art is difficult to effectively separate and recover impurities in waste lithium iron phosphate extraction slag, resulting in waste of Fe and P resources and environmental pollution. The existing methods are complex in technology and low in efficiency, making it difficult to prepare battery-grade iron phosphate.
The lithium iron phosphate extract slag is pre-pelletized and mixed with carbon material and additives, treated at high temperature under a reducing atmosphere, converted into a ferrophosphorus alloy by controlling the phase structure, and then prepared battery-grade iron phosphate by acid treatment and calcination.
It realizes efficient separation of impurities, prepares high-quality battery-grade iron phosphate, simplifies the process flow, improves production efficiency and product quality, and is suitable for industrial production.
Smart Images

Figure CN119750523A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of recycling waste battery materials, and specifically relates to the field of resource utilization of waste lithium iron phosphate lithium extraction slag. Background Art
[0002] Lithium iron phosphate batteries (LiFePO4) are widely used in mobile electronic devices, new energy vehicles, and energy storage base stations due to their excellent electrochemical properties and high safety. The life of power batteries for new energy vehicles is usually only 3 to 5 years, and there will inevitably be an explosive wave of scrapping of lithium iron phosphate batteries in the future. Due to its high value, lithium is usually preferentially extracted. At present, the lithium resources in lithium iron phosphate positive electrode materials are generally converted into lithium salt solutions by wet methods, and then recovered in the form of lithium carbonate, retaining FePO4 and other impurities in the lithium extraction slag. However, the Fe and P elements in the lithium extraction slag are very likely to cause heavy metal pollution and eutrophication of water bodies. If they are not properly disposed of, they will cause new environmental problems and greatly waste Fe and P resources.
[0003] If the impurities in lithium iron phosphate extraction slag can be effectively separated and the iron and phosphorus in the lithium iron phosphate extraction slag can be recovered in the form of battery-grade iron phosphate precursor, it will not only achieve high-value recycling of lithium iron phosphate extraction slag, but also promote the sustainable development of the lithium iron phosphate battery industry. At present, many experimental technologies have emerged for the recycling of lithium iron phosphate extraction slag, such as magnetic separation and acid leaching.
[0004] For example, a Chinese patent document with publication number CN 116588909 A discloses a method for preparing high-quality low-phosphorus iron concentrate from lithium iron phosphate slag in a short process, wherein the ferrophosphorus slag after lithium extraction from waste lithium iron phosphate is pulped, concentrated sulfuric acid is added, heated and stirred, reduction acid leaching is performed, heated and stirred, filtered, and washed to obtain an acid leaching solution and acid leaching residue, a reducing substance is added to the acid leaching solution, and then a buffer solution is added to adjust the hydrogen ions of the acid leaching solution, the heating and stirring are continued, the reaction is continued, and the ferrous phosphate solution and metal slag are obtained, the ferrous phosphate solution is acidified, heated and stirred, an oxidizing substance is added, filtered, and washed to obtain an amorphous ferric phosphate dihydrate.
[0005] The Chinese patent document with publication number CN 116425136 A discloses a method for purifying and recovering battery-grade iron phosphate from ferrophosphorus slag after lithium extraction, crushing the ferrophosphorus slag after lithium extraction, magnetic separation, adding acid solution for leaching, solid-liquid separation, supplementing phosphorus source or iron source, adding sodium nitrite and hydrogen peroxide for reaction, adjusting hydrogen ions, diluting, solid-liquid separation, and obtaining iron phosphate after high-temperature sintering. This technology can avoid the use of aluminum removal agents, fluoride salts and other substances, deeply remove metal ions, and obtain higher purity iron phosphate. However, the above two methods are complicated and do not effectively remove impurities, and the obtained iron phosphate does not meet the battery grade requirements.
[0006] A Chinese patent document with publication number CN 114195112 A discloses an innovative recycling method for waste lithium iron phosphate batteries. The method aims to efficiently extract and produce battery-grade lithium carbonate, iron phosphate or high-purity sodium phosphate products from waste batteries. In this process, the lithium element in the waste lithium iron phosphate batteries is first extracted using dilute acid leaching technology. Subsequently, the sodium phosphate is further extracted from the lithium iron phosphate slag after lithium extraction using an alkaline leaching method. However, in the subsequent treatment of the iron slag, although the roasting treatment is directly carried out to obtain iron concentrate, due to the insufficient deep removal of the phosphorus element, the main component of the obtained iron concentrate is high-phosphorus low-grade iron red, which to a certain extent limits its market added value and application scope.
[0007] A Chinese patent document with publication number CN 115784187 A discloses a new method for preparing anhydrous ferric phosphate from iron-phosphorus slag. The method uses alkaline leaching to effectively separate iron and phosphorus elements, so that the iron element is enriched in the slag, while the phosphorus element enters the alkaline leaching solution. Subsequently, the iron slag is treated with acid dissolution to generate an iron-containing acid solution; at the same time, the alkaline leaching solution is purified to obtain a pure phosphorus-containing alkaline solution. After the two types of solutions are mixed, basic iron phosphate is successfully generated. However, this process has not yet achieved deep removal of phosphorus from the iron slag, and the entire preparation process is relatively cumbersome, and further optimization is still needed in practical applications to improve efficiency and reduce costs.
[0008] In summary, among the resource utilization methods of waste lithium iron phosphate materials, magnetic separation is only suitable for slag samples with high iron content, and the recovery effect is poor. The acid leaching process consumes a lot of acid, the leaching effect of iron and phosphorus is not ideal, and the A1 in the leaching solution is 3+ and Fe 3+ The separation is difficult, which affects the preparation of iron phosphate. The prior art has not reported any idea or method for selectively preparing iron-phosphorus alloy from waste lithium iron phosphate slag and further regenerating it to prepare battery-grade iron phosphate. Summary of the invention
[0009] In view of the lack of prior art in the resource utilization of lithium iron phosphate extraction slag to prepare ferrophosphorus alloy and the technical gap in preparing iron phosphate based on the regeneration of ferrophosphorus alloy, the present invention provides a new method for preparing battery-grade iron phosphate from lithium iron phosphate extraction slag, aiming at converting the lithium iron phosphate extraction slag into the target phase ferrophosphorus alloy, and then chemically converting it to obtain high-quality battery-grade iron phosphate.
[0010] The present invention is the first in the industry to propose the idea of converting lithium iron phosphate slag into ferrophosphorus alloy, and further chemically converting the ferrophosphorus alloy to prepare iron phosphate. However, previous studies have shown that in order to successfully implement this technical idea, many technical difficulties need to be overcome. For example, it is necessary to overcome the difficulties in successfully realizing ferrophosphorus alloying and the low quality of alloying due to the special physical and chemical characteristics of lithium iron phosphate slag, and the difficulty in controlling the physical phase of ferrophosphorus alloy, resulting in the low quality of iron phosphate prepared by resource utilization. In view of the special implementation difficulties faced by the ideas described in the present invention, the present invention has conducted in-depth research and provided the following improvement means;
[0011] A method for preparing battery-grade iron phosphate from lithium iron phosphate slag, comprising the following steps:
[0012] Step 1:
[0013] The lithium iron phosphate extraction slag and the binder are mixed to form pellets and heat-treated to obtain pre-treated pellets;
[0014] Step 2:
[0015] The pretreated pellets, carbonaceous materials, additive A and additive B are mixed and heat-treated under a reducing atmosphere and a temperature T1; the slag is removed and separated to obtain a ferrophosphorus alloy;
[0016] The additive A comprises silicon dioxide or a component that can decompose silicon dioxide during the heat preservation stage; the additive B comprises metal M oxide and a component that can decompose metal M oxide during the heat preservation stage, wherein M comprises at least one of Ca, Mg, and Al; the weight ratio of the additive B to the additive A is 1.0 to 2.0;
[0017] The temperature T1 is above 1550°C;
[0018] Step 3:
[0019] The ferrophosphorus alloy is treated with acid and roasted to obtain battery-grade iron phosphate.
[0020] The present invention innovatively subjects the lithium iron phosphate extraction slag to the conditions described above, such as binder-assisted pelletization treatment, and then performs a heat preservation treatment with the carbonaceous material, additive A, and additive B in a reducing atmosphere and at the temperature T1. In this way, the lithium extraction slag can be recycled to prepare high-quality ferrophosphorus alloy based on a one-stage fusion process. In addition, it can also be beneficial to regulate the physical phase of the ferrophosphorus alloy so that it can be highly selectively converted into a physical and chemical structure and crystal structure that is beneficial to the synthesis of high-quality iron phosphate, thereby facilitating the subsequent recycling of high-quality battery-grade iron phosphate.
[0021] In the present invention, the lithium iron phosphate lithium extraction slag is the residue after the waste lithium iron phosphate positive electrode material is treated with lithium. The lithium extraction process can be conventional, for example, it can be water leaching, acid leaching, etc.
[0022] The lithium iron phosphate lithium extraction slag contains Fe, P and C as the main elements, with contents of 50-55%, 30-35% and 5-15% respectively, and the total content of other impurity elements such as Al, F and Ti can be 0.5%-5%; Fe and P mainly exist in the FePO4 phase.
[0023] The particle size of lithium iron phosphate slag is less than 200 mesh.
[0024] In the present invention, lithium iron phosphate lithium extraction slag and a binder are innovatively mixed to form balls and heat treated to achieve pelletization treatment, which can be coordinated with subsequent processes to achieve one-pot efficient synthesis of ferrophosphorus alloy. In addition, it is also beneficial to improve the one-pot separation selectivity and effect of impurities and ferrophosphorus alloy, and to regulate the phase structure characteristics of phosphate alloy, which is more conducive to the subsequent preparation of high-quality battery-grade iron phosphate.
[0025] In the present invention, the binder comprises bentonite and starch in a weight ratio of 0.5 to 2:1. The present invention shows that under the preferred composite binder, further synergy can be achieved, which is more conducive to adapting to the special physical and chemical characteristics of lithium extraction slag and more conducive to subsequent reactions to obtain Fe2P structure alloys, which helps to further improve the preparation of high-quality battery-grade iron phosphate.
[0026] The binder is 1-10% by weight of the lithium iron phosphate slag; further, it can be 3-5%.
[0027] The diameter of the pellets is 5~20mm.
[0028] The heat treatment temperature is 350 to 550°C, and may be 400 to 500°C.
[0029] The heat treatment time is 1~3h.
[0030] In the present invention, the lithium iron phosphate extraction slag is pelletized in advance and then heat-treated with the carbonaceous material, additive A and additive B in the reducing atmosphere and at the temperature T1, which is beneficial to the conversion of ferrophosphorus alloy and the regulation of its phase structure. In addition, it is also beneficial to the selective separation of impurities and ferrophosphorus alloy in the slag, and further beneficial to the subsequent preparation of high-quality battery-grade iron phosphate.
[0031] In the present invention, the carbonaceous material includes at least one of coke and charcoal.
[0032] The carbonaceous material accounts for 5-20% of the weight of the pellets, and can further account for 10-15%.
[0033] In the present invention, the amount of additive A is 1-3.5% of the weight of the pellets, and can further be 2-3%. The weight ratio of additive B to additive A is 1.2-1.5:1.
[0034] In the present invention, the reducing atmosphere is an atmosphere containing at least one reducing gas selected from hydrogen, methane and carbon monoxide; the content of the reducing gas is 5-30v%, and can further be 10-20v%.
[0035] The reducing atmosphere may also contain a diluent gas, such as nitrogen or at least one of an inert gas.
[0036] In the present invention, the temperature T1 is 1550-1700°C.
[0037] In the present invention, the holding time at temperature T1 is 1 to 4 hours, and can further be 2 to 3 hours.
[0038] In the present invention, in step 3, the ferrophosphorus alloy is placed in an acid solution for acid treatment.
[0039] The acid solution includes at least one of sulfuric acid, hydrochloric acid or nitric acid. The concentration of the solute in the acid solution is not particularly required, for example, it can be 0.1-2M.
[0040] The pH at the end point of the acid treatment reaction is controlled to be 1-3, and can further be 2-2.5.
[0041] In the present invention, solid-liquid separation is carried out after acid treatment, and the solid is washed with water, dried and then calcined to obtain the battery-grade iron phosphate.
[0042] The calcination temperature is 500-850°C, and can be 650-800°C.
[0043] The calcination time may be 1 to 5 hours, and further may be 2 to 4 hours.
[0044] In the present invention, the obtained iron phosphate can be subjected to conventional lithium calcination to obtain lithium iron phosphate material. For example, the temperature of lithium calcination can be 700-800°C and the time can be 5-15 hours. A small amount of conventional carbon source (such as sugar) can be added during the lithium calcination stage, and the addition amount can be, for example, 5-15%.
[0045] Beneficial Effects
[0046] The present invention proposes for the first time a new idea of converting waste lithium iron phosphate slag into ferrophosphorus alloy and preparing battery-grade iron phosphate based on the chemical conversion of ferrophosphorus alloy.
[0047] In view of the problems faced by the ideas of the present invention, the present invention innovatively pre-pelletizes the lithium extraction slag, and then performs heat preservation treatment under the joint control of carbonaceous material, additive A, additive B, reducing atmosphere and temperature. This not only can effectively synthesize iron-phosphorus alloy, but also is conducive to the highly selective separation of impurities in the slag and the iron-phosphorus alloy. Not only that, it can also unexpectedly adjust the physical phase and physicochemical structure of the ferrophosphorus alloy, so that it is highly synergistically coupled with the subsequent ferrophosphorus alloy chemical conversion process, thereby improving the preparation effect of the prepared battery-grade iron phosphate.
[0048] The process flow of the invention is relatively simple, easy to operate, and easy to realize industrialized production. The various links in the process flow are closely connected with each other, which can effectively improve production efficiency and product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is the technical roadmap for Example 1;
[0050] Figure 2 The XRD of the ferrophosphorus alloy obtained in Example 1;
[0051] Figure 3 This is the XRD of the iron phosphate obtained in Example 1;
[0052] Figure 4 XRD of lithium iron phosphate obtained in Example 1;
[0053] Figure 5 The first charge and discharge effect of the lithium iron phosphate obtained in Example 1 at 0.1C;
[0054] Figure 6 XRD of the ferrophosphorus alloy obtained in Example 2;
[0055] Figure 7 This is the XRD of the iron phosphate product finally obtained in Comparative Example 1;
[0056] Figure 8 This is the XRD of the iron phosphate product obtained in Comparative Example 2. DETAILED DESCRIPTION
[0057] The lithium iron phosphate lithium extraction slag described in the present invention can be a residue obtained by extracting lithium from waste lithium iron phosphate positive electrodes based on known means.
[0058] The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to the present invention may include the following steps:
[0059] Step a. Pelletization:
[0060] The lithium iron phosphate extraction slag is crushed, screened, mixed with a binder, pelletized, dried and preheated to obtain pretreated pellets;
[0061] Among them, after crushing and screening, particles with a particle size of less than 200 mesh are obtained; the binder is selected from bentonite, diatomaceous earth, starch or a mixture thereof, and the added amount is 1-10% of the slag weight; the pellet diameter is 5-20 mm; the drying temperature is 100-200°C; and the preheating temperature is 350-550°C.
[0062] Step b. Alloying:
[0063] The pretreated pellets are placed in a reactor, carbonaceous materials, additives A and B are added, and reduction reaction is carried out in a reducing atmosphere to remove the slag phase to obtain a high-purity ferrophosphorus alloy;
[0064] The carbonaceous material is selected from coke, charcoal or a mixture thereof; the carbonaceous material accounts for 5-20% of the weight of the pellets;
[0065] Additive A is silicon dioxide, and additive B includes at least one of calcium oxide, magnesium oxide, and aluminum oxide; the amount of additive A is 1-3.5% of the weight of the pellets; the weight ratio of additive B / additive A is controlled at 1.0-2.0; and stirring is performed at a speed of 10-50 r / min for 10-30 min.
[0066] The temperature of the reduction reaction is 1550~1700℃;
[0067] The reducing atmosphere is a mixture of an inert gas and a reducing gas, the inert gas is selected from argon, nitrogen or a mixture thereof, the reducing gas is selected from hydrogen, methane, carbon monoxide or a mixture thereof, and the volume fraction of the reducing gas is 5-30%; the reduction reaction time is controlled at 1-4 hours.
[0068] The atmosphere in the reactor is adjusted by controlling the flow ratio of the inert gas and the reducing gas, the inert gas flow is 1-10 m³ / h, and the reducing gas flow is 0.5-5 m³ / h. The reactor is selected from an electric arc furnace, an induction furnace or a resistance furnace.
[0069] Step c. Preparation of battery-grade iron phosphate from ferrophosphorus alloy:
[0070] The high-purity ferrophosphorus alloy is used as raw material and further processed by chemical methods to obtain battery-grade iron phosphate.
[0071] The chemical treatment method specifically includes: dissolving a high-purity ferrophosphorus alloy in an acid solution selected from sulfuric acid, hydrochloric acid or nitric acid; adjusting the pH value to 1-3; and obtaining battery-grade iron phosphate by precipitation, washing, drying and calcination at a calcination temperature of 500-850°C.
[0072] The high-purity ferrophosphorus alloy prepared by the method of the present invention has a phosphorus content of 15-25wt%, an iron content of 75-85wt%, a total impurity content of less than 0.5wt%, and has excellent processing performance and physical and chemical properties.
[0073] The battery-grade iron phosphate prepared by the method described in the present invention has a particle size of 1-10 μm, a specific surface area of 10-50 m² / g, a tap density of 1.0-2.0 g / cm³, a purity of more than 99%, and excellent electrochemical properties.
[0074] In the present invention, the lithium iron phosphate slag is the residue after the waste lithium iron phosphate positive electrode material is treated with lithium. In the lithium iron phosphate slag, Fe, P and C are the main elements, with contents of 50-55%, 30-35% and 5-15% respectively, and the total content of other impurity elements such as Al, F and Ti is 0.5%-5%; Fe and P mainly exist in the FePO4 phase. The particle size of the lithium iron phosphate slag is less than 200 mesh.
[0075] Embodiment 1:
[0076] Step a:
[0077] Take lithium iron phosphate lithium extraction slag with element proportions of 55% Fe, 30% P, 12% C and total impurities of 3%. Crush and screen the lithium iron phosphate lithium extraction slag to obtain particles with a particle size of less than 200 mesh. Add 3% bentonite as a binder, mix well and make pellets, with a pellet diameter of 10 mm. Dry the pellets at 150°C for 2 hours, and then preheat at 400°C for 1 hour to obtain pellets.
[0078] Step b:
[0079] The pretreated pellets were placed in an electric arc furnace, and the furnace temperature was controlled at 1550℃. The atmosphere in the furnace was a mixture of argon and hydrogen, with a hydrogen volume fraction of 10% and an inert gas flow rate of 5 m³ / h. 10% of the weight of the pellets was coke as a carbonaceous material, and 2% of the weight of the slag was silicon dioxide (additive A), calcium oxide was used as additive B, and the ratio of additive B / additive A was controlled at 1.2. The electromagnetic stirring was turned on, the stirring speed was 30 r / min, and the stirring was maintained for 20 min. The reduction reaction time was 2 hours to remove impurities in the melt. After refining, the melt was cast into a phosphorus-iron alloy ingot, and its XRD showed Figure 2 .
[0080] Step c:
[0081] The high-purity ferrophosphorus alloy ingot was dissolved in a 0.5-2M sulfuric acid solution, and the pH value was adjusted to 2 to precipitate. The precipitate was washed and dried, and then calcined at 700°C for 2-3 hours to obtain battery-grade iron phosphate. The XRD pattern of the material was Figure 3 .
[0082] Step d:
[0083] The iron phosphate and lithium carbonate prepared in step c are mixed in a stoichiometric ratio, and glucose and deionized water (liquid-to-solid ratio can be 5-10 ml / g) accounting for 5% of the total material (total weight of iron phosphate and lithium carbonate) are added, and stirred evenly. The mixture is wet-ground, usually using a sand mill for coarse grinding and fine grinding to obtain a precursor powder with a particle size of 1 μm. The precursor powder is pre-calcined at 350°C for 5 hours, and then kept at 800°C for 10 hours under inert atmosphere nitrogen protection to complete the reaction. After cooling, lithium iron phosphate is obtained. The XRD of the material is shown in FIG. Figure 4 .
[0084] Test results: The main phase of the ferrophosphorus alloy is Fe2P, accounting for 82% of the total, accompanied by the FeP phase, accounting for 18% of the total. The phosphorus content in the alloy is 21 wt%, the iron content is 78 wt%, the total impurity content is less than 0.3 wt%, and the Fe recovery rate is 97.5%. The particle size of battery-grade iron phosphate is 5 μm, the specific surface area is 25 m² / g, the tap density is 1.5 g / cm³, the purity reaches 99.5%, and the initial charge and discharge capacity of lithium iron phosphate at 0.1C reaches 152 mA·h. The electrochemical test chart is shown in Figure 5 .
[0085] Embodiment 2:
[0086] Step a:
[0087] Take lithium iron phosphate lithium extraction slag with element proportions of 53% Fe, 32% P, 10% C and total impurities of 5%. Crush and sieve the slag to a particle size of <120 mesh, add 5% diatomaceous earth binder by slag weight, mix well and make balls (ball diameter 22mm). Dry the balls at 200℃ for 5 hours and then preheat at 500℃ for 2.5 hours.
[0088] Step b:
[0089] The pellets were placed in a resistance furnace at a temperature of 1650°C. A mixture of argon and methane (methane volume fraction 18%) was introduced into the furnace. The inert gas flow rate was 12 m³ / h. Coke powder (15% by weight of the pellets), silicon dioxide (additive A) and calcium oxide (additive B) (3% by weight of the slag) were added. The ratio of additive B to additive A was controlled to be 1.5. Electromagnetic stirring was turned on (45 r / min, 40 min). After 3 hours of reduction reaction, the pellets were cast into ferrophosphorus alloy ingots. XRD showed Figure 6 .
[0090] Step c:
[0091] The ferrophosphorus alloy ingot is dissolved in a 0.5-1M nitric acid solution, and the pH is adjusted to 3.0 to precipitate. After washing and drying, the precipitate is calcined at 800°C for 2-2.5 hours to obtain battery-grade iron phosphate.
[0092] The prepared iron phosphate and lithium carbonate are mixed in a stoichiometric ratio, 8% of the total material mass of glucose and an appropriate amount of deionized water are added, and the mixture is stirred evenly. The mixture is wet-ground, usually using a sand mill for coarse and fine grinding, and the particle size is controlled at 1 μm. The precursor powder is pre-burned at 300°C for 4 hours to initially decompose the raw materials. Under the protection of an inert atmosphere of nitrogen, the pre-burned precursor is heated to 700°C and kept warm for 8 hours to complete the reaction. Lithium iron phosphate is obtained after cooling.
[0093] Test results: Fe2P is the main phase in the ferrophosphorus alloy, accounting for 84% of the total, accompanied by a small amount of FeP phase, accounting for 16% of the total, and the recovery rate of Fe is 98.3%. Compared with Example 1, FeP has partially transformed into Fe2P, with a phosphorus content of 23wt%, an iron content of 76 wt%, and a total impurity content of <0.4 wt%. The particle size of battery-grade iron phosphate is 8 μm, the specific surface area is 30 m² / g, the tap density is 1.6 g / cm³, and the purity reaches 99.7%; the specific capacity of lithium iron phosphate at the first charge and discharge of 0.1C reaches 147.8mA·h.
[0094] Example 3
[0095] Compared with Example 1, the only difference is that the binder in step a is changed, and the other operations and parameters are the same as Example 1. The experimental groups are:
[0096] Group A: The binder is starch, and its amount is the same as that in Example 1.
[0097] Group B: The binder is bentonite and starch in a weight ratio of 1:1, and the total amount of the binder is the same as that in Example 1.
[0098] The results are:
[0099] Group A: The iron recovery rate of the slag is 95.8%, the main phase of the ferrophosphorus alloy is Fe2P, with a content of about 81%, and the total impurity content is less than 0.4wt%. The particle size of battery-grade iron phosphate is 7 μm, the purity reaches 99.5%, and the initial charge and discharge capacity of lithium iron phosphate at 0.1C reaches 150 mA·h.
[0100] Group B: The iron recovery rate of the slag is 98.9%, the content of the ferrophosphorus alloy Fe2P phase is about 88%, and the total impurity content is less than 0.3wt%. The particle size of battery-grade iron phosphate is 4.3μm, the purity reaches 99.6%, and the first charge and discharge specific capacity of lithium iron phosphate at 0.1C reaches 154 mA·h.
[0101] Studies have shown that the use of bentonite / starch composite binders can optimize the spheroidization morphology of the slag, facilitate subsequent joint reduction, and synergistically improve the Fe2P phase of the ferrophosphorus alloy, thereby facilitating the subsequent preparation of lithium iron phosphate materials with excellent regeneration activity.
[0102] Comparative Example 1
[0103] Compared with Example 1, the only difference is that the slag is not subjected to the pelletization treatment in step a, but the lithium extraction slag and the binder are directly subjected to step b and subsequent treatments, and the other operations and parameters are the same as those in Example 1. The XRD of the finally obtained iron phosphate material is shown in Figure 7 .from Figure 7 It can be seen that the FePO4 in the lithium iron phosphate extraction slag is not completely decomposed and reduced, and the final product is composed of ferrophosphorus alloy and part of FePO4, and battery-grade iron phosphate cannot be obtained.
[0104] Comparative Example 2
[0105] Compared with Example 1, the only difference is that the furnace temperature in step b is controlled at 1500° C., and other operations and parameters are the same as in Example 1.
[0106] The XRD pattern of the iron phosphate material finally obtained is shown in Figure 8 .from Figure 8 It can be seen that the FePO4 in the lithium iron phosphate extraction slag is not completely decomposed and reduced, and the final product is composed of ferrophosphorus alloy and part of FePO4, and battery-grade iron phosphate cannot be obtained.
[0107] Comparative Example 3
[0108] Compared with Example 1, the only difference is that additive B is not added, and the amount of additive A is the same as the total weight of additives A+B in Example 1. Other operations and parameters are the same as in Example 1.
[0109] Test results: The P content in the ferrophosphorus alloy is only 18 wt%, the FeP phase accounts for more than 40%; the FeO content in the slag reaches 8.2%, and the iron recovery rate drops to 88% (Example 1 ≥ 95%).
[0110] Comparative Example 4
[0111] Compared with Example 1, the only difference is that in step a, water glass (Na2SiO3, added in an amount of 3%) is used as the binder. Other operations and parameters are the same as those in Example 1.
[0112] Test results: The compressive strength of the green balls is only 80 N / piece, and the cracking rate during the drying process is >30%; the iron recovery rate after pellet reduction is 91% (96.5% in Example 1), and the reaction contact area decreases due to the pulverization of the pellets.
Claims
1. A method for preparing battery-grade iron phosphate from lithium iron phosphate slag, characterized in that the steps include: Step 1: The lithium iron phosphate extraction slag and a binder are mixed to form pellets and heat-treated to obtain pre-treated pellets; the binder comprises at least one of bentonite, diatomaceous earth and starch; Step 2: The pretreated pellets, the carbonaceous material, the additive A and the additive B are mixed and heat-treated under a reducing atmosphere and a temperature T1; Deslagging and separation to obtain ferrophosphorus alloy; The additive A comprises silicon dioxide or a component that can decompose silicon dioxide during the heat preservation stage; the additive B comprises metal M oxide and a component that can decompose metal M oxide during the heat preservation stage, wherein M comprises at least one of Ca, Mg, and Al; the weight ratio of the additive B to the additive A is 1.0 to 2.0; The temperature T1 is above 1550°C; Step 3: The ferrophosphorus alloy is treated with acid and roasted to obtain battery-grade iron phosphate.
2. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: The lithium iron phosphate lithium extraction slag is the residue after the waste lithium iron phosphate positive electrode material is treated with lithium extraction; The particle size of lithium iron phosphate slag is less than 200 mesh.
3. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: The binder is 1-10% of the weight of lithium iron phosphate slag; The diameter of the pellets is 5~20mm; The heat treatment temperature is 350~550℃.
4. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: The carbonaceous material includes at least one of coke and charcoal; The carbonaceous material accounts for 5-20% of the pellet weight.
5. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: The dosage of additive A is 1-3.5% of the pellet weight.
6. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: The reducing atmosphere is an atmosphere containing at least one reducing gas selected from hydrogen, methane and carbon monoxide; the content of the reducing gas is 5-30%.
7. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: The temperature of temperature T1 is 1550~1700℃.
8. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag as claimed in claim 7, characterized in that: The holding time at temperature T1 is 1~4h.
9. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: In step 3, the ferrophosphorus alloy is placed in an acid solution for acid treatment; The acid solution includes at least one of sulfuric acid, hydrochloric acid or nitric acid; The pH at the end point of the acid-treated reaction is controlled at 1-3.
10. The method for preparing battery-grade iron phosphate from lithium iron phosphate slag according to claim 1, characterized in that: After the acid treatment, solid-liquid separation is performed, and the solid is washed with water, dried, and then calcined to obtain the battery-grade iron phosphate; The calcination temperature is 500-850°C.
Citation Information
Patent Citations
Recycling method of waste lithium iron phosphate battery
CN114195112A
Method for preparing anhydrous iron phosphate from iron phosphorus slag
CN115784187A
Method for purifying and recycling battery-grade iron phosphate from ferrophosphorus slag after lithium extraction
CN116425136A
Method for preparing iron phosphate from ferrophosphorus slag obtained after lithium extraction of waste lithium iron phosphate
CN116588909A
Method for recovering nickel-cobalt-manganese metal from waste battery lithium extraction material
CN111996377A